Vozes no ensino: o medo das crianças e sua relação com os saber na perspectiva das professoras - Camargo, Mauro Gomes de (Universidade Federal de São Carlos, 2024)
In a context in which the relationship with knowledge encompasses multifaceted dimensions, incorporating interactions with the world, with others and with oneself (Charlot, 2000). The aim of this research was to understand teachers' perceptions of children's relationship with knowledge as a function of their fears. To do this, we formulated a central question: what are the perceptions of three teachers who teach in the first year of elementary school about the fears expressed by their pupils? In addition, what is the knowledge enunciated in the face of these children's fears? This is a qualitative study with an empirical approach in two public schools in the municipality of Araraquara, São Paulo, Brazil, focusing on the dynamics of everyday school life. The theoretical basis for this research was the work of Charlot (1996, 2000, 2020). Data was collected through semi-structured interviews. To analyze the data, we adopted the “Balance of Knowledge” or “Inventory of Knowledge” approach, as proposed by Charlot (1996, 2009). This research has shown us various types of knowledge, among which we understand that, in the teachers' perception, there is a great diversity of fears faced by children in the school environment, which are related to knowledge. The teachers also identified different types of fears among their students, in addition to their own fears during their first years as students. However, this study has shown us that school is a web of knowledge, relationships and fears, in which observation, self-image and strategies are involved, in order to identify the fears of children in our schools.
Voices in teaching: children's fear and their relationship with knowledge from the teachers' perspective
Keywords: Medo das crianças; Relações com o saber; Escola; Children's fears; Relationships with knowledge; School; CIENCIAS HUMANAS::EDUCACAO